THE EFFECT OF PROFITABILITY, CAR, OEOI ON FIRM VALUE WITH CAPITAL STRUCTURE AS A MODERATING VARIABLE IN ISLAMIC BANKING IN ASIA - Mawardi, M. Ilyas; Jaya, Tiara Juliana (JURNAL DIMENSI, 2024)
Islamic economics came back when the new economic era had begun to develop. The emergence of Islamic Banking followed this. Islamic Banking is expected to make the economy of countries in the world even better. This study aims to analyze the effect of profitability, CAR, and OEOI on firm value, as well as the moderating function of capital structure. This study uses quantitative methods with panel data regression analysis techniques with Eviews 12. The sample of this study includes 11 Islamic banks in Asia using secondary data taken from each official website of each Islamic bank. Based on research results, the value of Sharia banking companies in Asia is significantly influenced by profitability. CAR and OEOI do not affect the value of Sharia banking companies. Capital structure cannot mitigate the impact of profitability and CAR on company value. However, the effect of OEOI on company value can be mitigated by capital structure.